First report of upfront treatment with Gefitinib in comparison with chemotherapy in advanced non-small cell lung cancer patients from south India: Analysis of 120 patients - Robert A Louis; Rejiv Rajendranath; Prasanth Ganesan; T G Sagar; Arvind Krishnamurthy (Indian Journal of Medical and Paediatric Oncology)
Background: Lung cancer is the most common cause of cancer deaths in males and sixth among females in south India. Lung cancer is being increasingly recognized among non-smokers. Materials and Methods: Stage IIIB and IV advanced non-small cell lung cancer (NSCLC) patients (n=120) treated from January 2009 to December 2010 were retrospectively analyzed. Baseline clinical parameters, treatment protocol, response to therapy and survival were noted. Decision to use upfront Gefitinib was based on parameters like female sex, non-smoking status, adenocarcinoma histology and poor PS. Progression-free survival (PFS) and overall survival (OS) were analyzed by the Kaplan Meier method and prognosis by log rank test and Cox regression. Results: Baseline parameters: median age: 60 years (22-78 years); male sex: 83 (69.2%); Stage IV: 95(79.2%); adenocarcinoma: 109 (90.8%); smokers: 66 (55%); PS 2/3: 65(54.2%); first-line therapy: Gefitinib: 47 (39.2%), chemotherapy: 73 (60.8%). Among those progressing after chemotherapy, 17 (23%) received second-line Gefitinib. After a median follow-up of 7.5 months (1-26 months), median PFS and OS were 5 months (0-23 months) and 7.5 months (1-26 mo), respectively. On univariate analysis, PFS was significantly improved for non-smokers (7 months vs 4 months, P=0.010), females (7 months vs 5 months, P=0.024) and upfront treatment with Gefitinib (10 months vs 4 months, P=0.014). The only significant factor that affected OS was female sex (18 months vs 9 months, P=0.042). No factors were significant on multivariate analysis. Among PS 2/3 patients, PFS was significantly higher with Gefitinib (n=36) than with single-agent chemotherapy (n=29) [median PFS of 10 months vs 4 months (P=0.017)]. Conclusion: In the largest series on the use of first-line Gefitinib from India, we found it to be a useful agent in the treatment of NSCLC, especially in females patients with poor PS and non-smokers, even without Epidermal Growth Factor Receptor (EGFR) mutation testing. Second-line Gefitinib may have negated the OS differences. However, EGFR mutation studies may help in further individualization of therapy.